2017
DOI: 10.29252/johe.6.2.114
|View full text |Cite
|
Sign up to set email alerts
|

Health problems among garment factory workers: A narrative literature review

Abstract: Background: Garment factories in India contribute to the economic growth and it is the second largest sector for employment. Many unskilled laborers from rural location work in this sector. The common jobs handled by them are sewing, ironing, packing and lifting heavy loads which are monotonous, continuous and prolonged. Working for a long period of time without rest, absence of personal protective equipment and inadequate provision of ergonomic facilities at workplace leads to major health-related issues amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…Textile and clothing are considered as the oldest, largest and most global industries in the world and in India, it is also considered as the second largest employment sectors [1] . According to ILO estimates, at least 2 million deaths per year are accounted to occupational diseases and injuries [2] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Textile and clothing are considered as the oldest, largest and most global industries in the world and in India, it is also considered as the second largest employment sectors [1] . According to ILO estimates, at least 2 million deaths per year are accounted to occupational diseases and injuries [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the workers with repetitive nature of work due to the physical demands are prone to get physical, psychological and nutritional health problems [6,7] . The most common health hazards are respiratory problems, cardio vascular diseases, gastrointestinal diseases, gynecological diseases, and neurological, musculoskeletal and nutritional problems [1] . Approximately 60% of the population employed in the garment industry is women [1] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted in a different part of India among factory workers have revealed that musculoskeletal problem is the most common morbidity among the factory workers and genitourinary problem among the female factory workers. [ 8 ] In the present study, the most common morbidity among the healthcare worker is a one or other type of chronic disease. Hypertension was the most prevalent chronic disease in 12.2%of the study participants, the prevalence of the disease is below the national average of 29.8% and 34.5% for East India.…”
Section: Discussionmentioning
confidence: 90%
“…The literature review revealed that there have been studies to know the health status of different workers like factory workers and migrant workers and health care worker like doctors and nurses working in hospitals. [ 6 7 8 9 10 11 12 ] But there is paucity in literature in revealing the morbidity or health status of the grassroot-level primary care health workers in India or abroad except studies related to the work stress or mental health of the frontline health care workers. [ 13 14 ] With this background in mind, the present study was conceived to know the morbidity profile, nutritional status, and mental health status of the grass-root level health care workers in an urban area of Odisha.…”
Section: Introductionmentioning
confidence: 99%